Effects of abiotic stress on gene transcription in European beech: ozone affects ethylene biosynthesis in saplings of Fagus sylvatica L. - Betz GA; Gerstner E; Olbrich M; Winkler JB; Langebartels C; Heller W; Sandermann H; Ernst D (iForest - Biogeosciences and Forestry, 2009)
The influence of ozone (150-190 nl L-1; 8h/d) on transcription levels of genes involved in the biosynthesis of the stress hormone ethylene, and its precursor 1-aminocyclopropane-1-carboxylate (ACC), was analysed in leaves of European beech saplings. Ozone-induced leaf lesions appeared 7 weeks after onset of ozone exposure. Cell lesion formation was preceded by persistent increases in ethylene emission, in the level of its malonylated precursor ACC, and in the transcript levels of specific ACC synthase 1 (ACS1), ACS2, ACC oxidase 1 (ACO1), and ACO2. Our results demonstrate that mechanisms similar to those operating in herbaceous plants may determine beech saplings responses to ozone exposure.